HASIL BELAJAR PAI DENGAN MENGGUNAKAN MEDIA POWER POINT DI SDN 07 GUNUANG MALINTANG - Edrio Mahendra; Zulfani Sesmiarni; Rodi Rodi; Rosyahela Rosyahela (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research is entitled “Improving Islamic Education Learning Outcomes by Using Power Point Media at SDN 07 Gunuang Malintang”. The main purpose of this research is to improve the learning outcomes of students in Islamic Religious Education (PAI) subjects in class IV SDN 07 Gunuang Malintang through the use of Power Point media. The problem raised in this study is whether Power Point media is effective in improving the learning outcomes of fourth grade PAI students. This research uses the Classroom Action Research (PTK) method which is a type of qualitative research. The research subjects were fourth grade students of SDN 07 Gunuang Malintang, with data collection methods through observation and tests. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The success indicator used is the achievement of the Minimum Completeness Criteria (KKM) with a score of 70. The results showed that the application of Power Point media was able to significantly improve student learning outcomes. In the early stages (pre-cycle), only 40% of students achieved scores above the KKM. After cycle I, the percentage of students who reached the KKM increased to 67%, and in cycle II it rose again to 87%. In cycle III, the percentage of students who achieved scores above the KKM reached 93.3%. Based on these results, it can be concluded that the use of Power Point media in learning Islamic Religious Education is effective in improving student learning outcomes. The significant increase from cycle to cycle shows that Power Point media has a positive impact on the understanding and learning achievement of grade IV students at SDN 07 Gunuang Malintang.